Donor-specific antibodies following liver and intestinal transplantation: Clinical significance, pathogenesis and recommendations. (4th May 2019) - Wozniak, Laura J.; Venick, Robert S.
Abstract: A growing body of evidence shows that donor-specific antibodies (DSA) are associated with rejection and allograft failure following both liver and intestinal transplantation. However, data have clearly shown that not all DSA are injurious. The reasons for this remain unclear but appear to be multifactorial, impacted by clinical factors such as immunosuppression and infection as well as immunologic factors such as HLA expression and donor-specific antibodies affinity. Establishing a diagnosis of antibody-mediated rejection (AMR) remains clinically challenging, especially given that AMR can present as either acute or chronic graft dysfunction. These observations highlight the need for a better understanding of the immune mechanisms by which DSA and AMR contribute to rejection and allograft failure. This review focuses on current knowledge of DSA and AMR in liver and intestinal transplant recipients and specifically highlights the clinical impact, prevalence, and pathogenesis.